2015
DOI: 10.5946/ce.2015.48.4.340
|View full text |Cite
|
Sign up to set email alerts
|

Single Cavernous Hemangioma of the Small Bowel Diagnosed by Using Capsule Endoscopy in a Child with Chronic Iron-Deficiency Anemia

Abstract: Cavernous hemangiomas of the gastrointestinal tract are extremely rare. In particular, the diagnosis of small bowel hemangiomas is very difficult in children. A 13-year-old boy presented at the outpatient clinic with dizziness and fatigue. The patient was previously diagnosed with iron-deficiency anemia at 3 years of age and had been treated with iron supplements continuously and pure red cell transfusion intermittently. Laboratory tests indicated that the patient currently had iron-deficiency anemia. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…The diameter of the lesions varied from 0.8 cm to 50 cm. Most studies showed suspicious findings on capsule endoscopy and the lesions were resected surgically or endoscopically [ 1 , 5 - 7 , 9 - 14 , 16 - 18 ]. Ejtehadi et al demonstrated a hemangioma on scintigraphy and CT enterography while no positive finding was found on capsule endoscopy [ 15 ]; another reported case was diagnosed with contrast-enhanced CT and MRI preoperatively [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of the lesions varied from 0.8 cm to 50 cm. Most studies showed suspicious findings on capsule endoscopy and the lesions were resected surgically or endoscopically [ 1 , 5 - 7 , 9 - 14 , 16 - 18 ]. Ejtehadi et al demonstrated a hemangioma on scintigraphy and CT enterography while no positive finding was found on capsule endoscopy [ 15 ]; another reported case was diagnosed with contrast-enhanced CT and MRI preoperatively [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemangiomas in the small intestine are rare benign tumors and account for approximately 5% of all GI neoplasms. 2 GI hemangiomas typically occur in the ileum and are rarely found in children. A literature review revealed only 9 known cases (Table).…”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed only 9 known cases (Table). [2][3][4][5][6][7][8] Patients with GI hemangioma present with melena and hematochezia, sometimes causing severe anemia, or with symptoms of obstruction. Patients may also exhibit abdominal discomfort, abdominal pain, dizziness, nausea, vomiting, fatigue, general weakness, and malaise.…”
Section: Discussionmentioning
confidence: 99%
“…Выполненные операции не отличались большим разнообразием [4][5][6] Гемангиомы печени -редкое заболевание у детей [7][8][9]. Гемангиомы могут быть небольшими и могут достигать очень больших размеров, быть красного, синего цвета, бугристыми, консистенция плотная или мягко-эластичная.…”
Section: таблица 1 локализация гемангиом органов брюшной полостиunclassified